Analisis Penerapan Akuntansi dalam Pengelolaan Dana Simpan Pinjam RT di Fafinesu B, Kecamatan Insana Fafinesu, Kabupaten TTU - Neno, Modesta; Balenaen, Amanda Leontin Barek; Jemadu, Santhya Evita; Lian, Yohanes Pemandi (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Several Neighborhood Associations in Fafinesu B Village have formed savings and loan business groups with the aim of providing loans to members or other residents who need urgent funds. All financial management processes are carried out simply which makes the results obtained relatively minimal. This study was conducted with the aim of analyzing the application of accounting principles in the management of savings and loan funds. The research method used is a descriptive qualitative approach and data collection is carried out using interview, observation and questionnaire techniques. The results indicate that all RT savings and loan business groups have not applied general accounting principles. Financial records are limited to transactional records of loans per person and their installments and are not accompanied by profit and loss reports, balance sheets, financial statements. At the end of the period when the management is accountable, the final balance along with the final profit obtained verbally and the focus of the group members is the final results obtained without going through the process of supervision and control so that problems are often found, including some groups getting less profits, some borrowers are unable to repay the loan. Some members do not get loans and even some groups cannot continue the business in the next period. Simple accounting recording training needs to be carried out for savings and loan fund managers and members so that in their operations this business can implement a systematic and effective accounting system in order to reduce problems.